Comparative investigation of the pathogenicity of three Mycobacterium tuberculosis mutants defective in the synthesis of p-hydroxybenzoic acid derivatives - Stadthagen, Gustavo; Jackson, Mary; Charles, Patricia; Boudoua, Frédéric; Barilonea, Nathalie; Huerree, Michel; Constant, Patricia; Liav, Avraham; Bottova, Iveta; Nigou, Jérome; Brandod, Thérèse; Puzo, Germain; et al. (Elsevier, 2006)
p-Hydroxybenzoic acid derivatives (p-HBADs) are glycoconjugates secreted by all Mycobacterium tuberculosis isolates whose contribution to pathogenicity remains to be determined. The pathogenicity of three transposon mutants of M. tuberculosis deficient in the biosynthesis of some or all forms of p-HBADs was studied. Whilst the mutants grew similarly to the wild-type strain in macrophages and C57BL/6 mice, two of the mutants induced a more severe and diffuse inflammation in the lungs. The lack of production of some or all forms of p-HBADs in these two mutants also correlated with an increased secretion of the pro-inflammatory cytokines tumour-necrosis factor α, interleukin 6 and interleukin 12 in vivo. We propose that the loss of production of p-HBADs by tubercle bacilli results in their diminished ability to suppress the proinflammatory response to infection and that this ultimately provokes extensive pulmonary lesions in the C57BL/6 model of tuberculosis infection.